DAYA REGENERASI PLBs ANGGREK DENDROBIUM VAR. JACQUELINE THOMAS x WALTER OUMAE DAN KUMALA AGRIHORTI PADA JENIS MEDIA KULTUR IN VITRO DENGAN PENAMBAHAN AIR KELAPA - Sri Rianawati; Sulastri Isminingsih; Nuniek Herminta; Luqyana Ulfa Riyadi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Dendrobium is the epiphytic orchid and high demand because of its long-lasting freshness, color variants, shape, and high productivity. The addition of organic complex Coconut Water (CW) to the in vitro media such as MS and VW because in general organic complex compounds are sources of sugars, vitamins, growth regulators, and amino acids. The purpose of this study was to obtain the best media for plantlet regeneration from PLBs of Dendrobium orchids var. JTWO and var. Kumala Agrihorti. This study used a Completely Randomized Design consisting of two factors with five replications. The combination of planting media with the addition of coconut water was consist of 10 levels, ½ MS+0 ml/l CW, ½ MS+75 ml/l CW, ½ MS+100 ml/l CW, ½ MS+125 ml/l CW, ½ MS+150 ml/l CW, VW+0 ml/l CW, VW+75 ml/l CW, VW+100 ml/l CW, VW+125 ml/l CW and VW+150 ml/l CW. The results showed that the variety treatment gave a significant effect on the percentage of PLBs regeneration, the number of shoots, and the increase in plantlet height. The treatment of media gave a significant effect on the percentage of PLBs regeneration, percentage of PLBs life, the number of leaves, and the number of roots. The interaction between treatments significantly affects the percentage of PLBs regeneration.